A Comparison of Solution Methods for Real Business Cycle Models - Jürgen Ehlgen (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1998)
This paper discusses solution procedures for real business cycle (RBC) models. First, we show that the most often used solution methods, the linear-quadratic approximation, the Lagrange multiplier, and the Euler equation approach all lead to the same decision function. Second, we demonstrate that deterministic and stochastic detrending methods which are used to transform the growing model economy to a stationary one, lead to the same model solution, no matter if the technology process has a unit root or not. Third, we show that contrary to statements in the literature the numerical value of the growth rate of the model can have substantial effects on the model results.
Keywords: 330